Frans Floris (1519/20-1570) : imagining a Northern Renaissance - Wouk, Edward H. (Brill's studies in intellectual history, 2018)
Frans Floris de Vriendt radically transformed Netherlandish art. His monumental mythologies introduced a new appreciation for the heroic nude to the Low Countries and his religious art challenged standards of decorum. Born into a family of sculptors and architects, Floris refashioned his art through travel, first studying with the humanist painter Lambert Lombard in Liege and then continuing on to Italy. These experiences defined the hybridizing novelty of his art, forged by juxtaposing antique and modern, Italian and Northern sources. This book maps Floris's hybrid style onto shifting conceptions of cultural, religious, and political identity on the eve of the Dutch Revolt. It explores his collaborations and rivalries, engagement with artistic theory, hierarchical workshop, and revolutionary use of print.